2021
DOI: 10.3389/ffgc.2021.689836
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Resource Dynamics in Mast Years for European Beech and Oak—A Continental Scale Analysis

Abstract: Resource allocation to different plant tissues is likely to be affected by high investment into fruit production during mast years. However, there is a large knowledge gap concerning species-specific differences in resource dynamics. We investigated the influence of mast years on stem growth, leaf production, and leaf carbon (C), nitrogen (N), and phosphorus (P) concentrations and contents in Fagus sylvatica, Quercus petraea, and Q. robur at continental and climate region scales using long-term data from the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 82 publications
2
15
0
Order By: Relevance
“…Beech DM100 and LA both increased with autumn temperatures of the preceding year. This is in line with the study of Nussbaumer et al (2021), who found that high temperatures in September and October of the preceding year influenced the annual leaf production of beech. Nussbaumer et al (2021) used the total leaf mass in litterfall in their model, and therefore they could not determine whether enhanced leaf biomass resulted from the production of more leaves or from an increase in dry mass of individual leaves.…”
Section: Common and Different Responses Of Leaf Morphological Traits To Climatic Effects In Beech And Sprucesupporting
confidence: 92%
See 3 more Smart Citations
“…Beech DM100 and LA both increased with autumn temperatures of the preceding year. This is in line with the study of Nussbaumer et al (2021), who found that high temperatures in September and October of the preceding year influenced the annual leaf production of beech. Nussbaumer et al (2021) used the total leaf mass in litterfall in their model, and therefore they could not determine whether enhanced leaf biomass resulted from the production of more leaves or from an increase in dry mass of individual leaves.…”
Section: Common and Different Responses Of Leaf Morphological Traits To Climatic Effects In Beech And Sprucesupporting
confidence: 92%
“…It should be noted that many of the leaf samples in 2019 were damaged and had perforation holes, which might also skew our findings toward a higher LMA. The effects of the summer and autumn climate (i.e., VPD, T) in the preceding year confirm the existence of legacy effects on leaf primordia buds that influence the development of beech leaves in the current year (e.g., Nussbaumer et al, 2021). The reason for the negative effect of winter temperatures on LMA in our temporal analysis remains uncertain, but might be related to temperature-driven shifts in the timing of leaf phenology (Clark et al, 2014).…”
Section: Common and Different Responses Of Leaf Morphological Traits To Climatic Effects In Beech And Sprucesupporting
confidence: 68%
See 2 more Smart Citations
“…understand how variable allocation to reproduction influences carbon sequestration above and belowground, and how this varies between species and across environmental gradients(Bajocco et al, 2021;Nussbaumer et al, 2021;Oddou-Muratorio et al, 2021;Zhang et al, 2022). Related work can use MASTREE+ data combined with F I G U R E 3 Distribution of time-series in MASTREE+ according to local climate (Worldclim v2.1, 30 arcsecond resolution,Mosier et al, 2014).…”
mentioning
confidence: 99%